Five little monkeys with nothing to do - Christelow, Eileen (New York : Clarion Book, 1996)
Five little monkeys are bored, but their mother has them clean up the house for Aunt Bessie's visit.
Wilson's Children
Elem. School Library Collection
School Library Journal
2.4
K-3
Keywords: Monkeys -- Fiction; House cleaning -- Fiction; Monkeys -- Fiction; House cleaning -- Fiction